2010
DOI: 10.1186/1471-2334-10-325
|View full text |Cite
|
Sign up to set email alerts
|

"Pee-in-a-Pot": acceptability and uptake of on-site chlamydia screening in a student population in the Republic of Ireland

Abstract: BackgroundThe aim of the study was to explore the acceptability and uptake of on-campus screening using a youth friendly approach in two Third Level higher education institutions (HEIs). This study is part of wider research exploring the optimal setting for chlamydia screening in Ireland.MethodsMale and female students were given the opportunity to take a free anonymous test for chlamydia during a one week programme of "pee-in-a-pot" days at two HEI campuses in the West of Ireland. The study was set up after e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Male participants frequently commented on the simplicity of urinating in a cup and the convenience of a class-wise approach with everyone getting tested. Adolescent males are more likely to accept STI testing if the testing procedures are convenient [17,21,22] and if they feel that confidentiality is maintained [23]. Individual provider characteristics may also impact on their decision [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Male participants frequently commented on the simplicity of urinating in a cup and the convenience of a class-wise approach with everyone getting tested. Adolescent males are more likely to accept STI testing if the testing procedures are convenient [17,21,22] and if they feel that confidentiality is maintained [23]. Individual provider characteristics may also impact on their decision [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Sexual health promotion advice can be provided on websites or through telephone counselling. Young people value the anonymity, convenience and accessibility of testing without the need for a consultation and the informal and nonmedical approach [51,52]. Emerging evidence suggesting that testing via the Internet is increasing and may appeal to young people at high risk of infection; a US study reported higher positivity from Internet screens than tests taken from contraceptive services [53].…”
Section: Strategies To Control Chlamydia That Focus On Populationsmentioning
confidence: 97%
“…In a program that conducted screening in 2 consecutive school years, 53% of participants in the first year were retested in the next year, and the repeat CT positivity was 21.1%. These 4 programs used various student events for screening such as orientation week 29 ; sexual health awareness and guidance week 48 ; school health fair 46 ; orientation week; market stalls; band and bar nights; sporting events; scavenger hunts; and Halls of Residence. 36 Event-Based Screening.…”
Section: Findings By Program Typementioning
confidence: 99%
“…36 Event-Based Screening. 48 In one program, test packs were available in bathrooms as well as distributed by volunteers with specimen collection boxes placed inside toilet areas. 31 Screening was promoted through advertisements including posters 29 ; posters, student media, SMS, Web sites, and education sessions 31 ; and posters, leaflets, media, radio, e-mail, and newspapers.…”
Section: Findings By Program Typementioning
confidence: 99%
See 1 more Smart Citation